The Analysis on the Characteristics of Decorative Patterns of Bronze Mirrors in the Song, Liao and Jin Dynasties in China - Linjing , Dang; Sawatdee, Yodkwan (Journal of Roi Kaensarn Academi, 2024)
The research objectives of this article are: (1) To provide designers with design ideas and research basis through the collection, summary, arrangement and analysis of traditional decorative patterns on Chinese bronze mirrors. (2) From the perspective of art design, combined with the method of image analysis, explore the characteristics of bronze mirror patterns and spread the knowledge of traditional Chinese decorative art culture. (3) On this basis, analyze the characteristics of the decorative patterns of bronze mirrors in the Song, Liao and Jin dynasties of my country, and put forward more suggestions. This article employs qualitative research methods, including questionnaire surveys, field observations, and case analyses, among others. The research population the local student and tourist population at the Datong Liao, Jin, and Yuan Culture and Art Museum. It combines both paper and electronic questionnaires, as well as cameras and video recorders as research instruments. A total of 211 paper questionnaires and 653 online questionnaires were collected to analyze the target group's familiarity and interest in the decorative patterns of bronze mirrors during the Song, Liao, and Jin Dynasties of China. Through analysis and research on the decorative patterns of bronze mirrors from the Song, Liao and Jin dynasties, the results show that the decorative patterns in the Song Dynasty had a new look, emphasizing practicality. The mirror back patterns no longer deliberately pursued exquisiteness, and most of the patterns had simple lines. A typical feature of bronze mirror decoration in the Liao Dynasty is symmetry, which is highly realistic and worldly. The decorative patterns on bronze mirrors of the Liao Dynasty reflect the rough and heroic characteristics of Liao culture. The typical characteristics of the bronze mirror art of the Jin Dynasty are innovation, rich themes and expression techniques, which ultimately put the bronze mirror art of the Jin Dynasty on the road of innovation.